2016
DOI: 10.1097/mjt.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Reactivity Unit in Predicting Risk of Bleeding in Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Bleeding is a common complication of cardiac surgery, accounting for a significant proportion of the total transfusions performed in the United States and Europe. The relationship between platelet reactivity, bleeding, and other adverse events after coronary artery bypass graft surgery (CABGS) has been incompletely characterized. This study investigated the relationship between platelet reactivity and bleeding as a clinical outcome after successful CABGS. A total of 238 patients who underwent CABGS were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A considerably more conservative range of 179–200 units (upper limit, 238) was proposed for patients undergoing PCI based on ischemic or bleeding events [ 25 , 26 ]. In addition, a range of 180–200 (upper limit, 230) was suggested for patients with coronary artery bypass grafting (CABG) [ 27 , 28 ]. Furthermore, the developers of the VerifyNow ® P2Y12 assay have specified 194–418 as the normal PRU range, which can be measured ≥6 hours post bolus drug administration (Accumetrics).…”
Section: Discussionmentioning
confidence: 99%
“…A considerably more conservative range of 179–200 units (upper limit, 238) was proposed for patients undergoing PCI based on ischemic or bleeding events [ 25 , 26 ]. In addition, a range of 180–200 (upper limit, 230) was suggested for patients with coronary artery bypass grafting (CABG) [ 27 , 28 ]. Furthermore, the developers of the VerifyNow ® P2Y12 assay have specified 194–418 as the normal PRU range, which can be measured ≥6 hours post bolus drug administration (Accumetrics).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be explained by the fact that the mechanism of aspirin-related bleeding adverse events is not yet fully understood. Some authors suggest that the prophylactic efficacy of aspirin and the risk of bleeding related to this drug may be influenced by a phenomenon of platelet hyper-reactivity (17). However, further research is necessary to establish the real impact of platelet hyper-reactivity on the aspirin safety profile in ESRD patients.…”
Section: Chronic Kidney Disease (Ckd) Is a Pathology Defined By A Decmentioning
confidence: 99%
“…This discrepancy highlights the fact that the mechanism of aspirin-related bleeding events is not yet fully understood. Some authors have suggested that the prophylactic efficacy of aspirin and risk of bleeding related to this drug may be influenced by a phenomenon of platelet hyperreactivity [ 16 ]. However, further research is necessary to establish the real impact of platelet hyperreactivity on aspirin’s safety profile in patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%